Potential of Legume–Brassica Intercrops for Forage Production and Green Manure: Encouragements from a Temperate Southeast European Environment - Jeromela, Ana M.; Mikić, Aleksandar M.; Vujić, Svetlana; Ćupina, Branko; Krstić, Đorđe; Dimitrijević, Aleksandra; Vasiljević, Sanja; Mihailović, Vojislav; Cvejić, Sandra; Miladinović, Dragana (Frontiers in Plant Science, 2017)
Legumes and brassicas have much in common: importance in agricultural history, rich biodiversity, numerous forms of use, high adaptability to diverse farming designs, and various non-food applications. Rare available resources demonstrate intercropping legumes and brassicas as beneficial to both, especially for the latter, profiting from better nitrogen nutrition. Our team aimed at designing a scheme of the intercrops of autumn- and spring-sown annual legumes with brassicas for ruminant feeding and green manure, and has carried out a set of field trials in a temperate Southeast European environment and during the past decade, aimed at assessing their potential for yields of forage dry matter and aboveground biomass nitrogen and their economic reliability via land equivalent ratio (LER). This review provides a cross-view of the most important deliverables of our applied research, including eight annual legume crops and six brassica species, demonstrating that nearly all the intercrops were economically reliable, as well as that those involving hairy vetch, Hungarian vetch, Narbonne vetch and pea on one side, and fodder kale and rapeseed on the other, were most productive in both manners. Feeling encouraged that this pioneering study may stimulate similar analyses in other environments and that intercropping annual legume and brassicas may play a large- scale role in diverse cropping systems, our team is heading a detailed examination of various extended research.